2017
DOI: 10.3389/fpsyg.2017.00153
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Modeling of Affective Qualities of Musical Instrument Sounds across Pitch Registers

Abstract: Composers often pick specific instruments to convey a given emotional tone in their music, partly due to their expressive possibilities, but also due to their timbres in specific registers and at given dynamic markings. Of interest to both music psychology and music informatics from a computational point of view is the relation between the acoustic properties that give rise to the timbre at a given pitch and the perceived emotional quality of the tone. Musician and nonmusician listeners were presented with 137… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 43 publications
5
60
3
Order By: Relevance
“…Presenting recorded instruments playing a single pitch (D#4), Eerola, Ferrer Flores, and Alluri (2012) found a significant negative correlation between high-frequency to low-frequency energy ratio and valence ratings; in this particular experiment, the correlation between valence (pleasant/unpleasant) and preference (like/dislike) ratings was so high ( r = 0.97) as to warrant treating the two constructs synonymously. In a similar study, McAdams, Douglas, and Vampala (2017) found a significant correlation between instrument family and liking across multiple pitch registers. Finally, Wallmark, Iacoboni, Deblieck, and Kendall (2018) found a significant negative correlation between subjective ratings of “noisiness” and liking (referred to in the study as “valence”) in 400-ms excerpts of popular music.…”
mentioning
confidence: 71%
“…Presenting recorded instruments playing a single pitch (D#4), Eerola, Ferrer Flores, and Alluri (2012) found a significant negative correlation between high-frequency to low-frequency energy ratio and valence ratings; in this particular experiment, the correlation between valence (pleasant/unpleasant) and preference (like/dislike) ratings was so high ( r = 0.97) as to warrant treating the two constructs synonymously. In a similar study, McAdams, Douglas, and Vampala (2017) found a significant correlation between instrument family and liking across multiple pitch registers. Finally, Wallmark, Iacoboni, Deblieck, and Kendall (2018) found a significant negative correlation between subjective ratings of “noisiness” and liking (referred to in the study as “valence”) in 400-ms excerpts of popular music.…”
mentioning
confidence: 71%
“…The finding that noisy timbre drives limbic activity more so than normal timbres produced by the same sound generators may have implications for our understanding of the role of timbre in affective response to music more generally (Eerola et al, 2012;McAdams et al, 2017). We theorize that part of the pleasure derived from music with prominent noisy timbres may be a case of ''limbic reversal'' as theorized by Huron (2006).…”
Section: Limbic and Insula Response To Noisy Timbrementioning
confidence: 82%
“…Filipic et al (2010), for example, found no difference between musicians and non-musicians in the perception of brief timbral stimuli. On the other hand, McAdams et al (2017) reported a three-way interaction between training, pitch register, and instrument family in perceptual evaluations of timbre. Although our stimuli were controlled for pitch, it is possible that familiarity affected behavioral evaluations and neural activity (Margulis et al, 2009).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, there is a rich literature on audio features associated with computer-based instrument identification (Joder et al, 2009 ), genre classification (e.g., Andén and Mallat, 2011 ), the prediction of affective qualities (Laurier et al, 2009 ; McAdams et al, 2017 ), or more general aspects of the perception of audio excerpts (Alluri and Toiviainen, 2010 ). Audio features are most commonly derived from the Short-Time Fourier Transform of the music signal, from which spectral or temporal statistics are computed.…”
Section: Introductionmentioning
confidence: 99%